Coronary artery bypass graft surgery: The fourth school of thought? / Mohd Zamrin Dimon - Dimon, Mohd Zamrin (Universiti Teknologi MARA Cawangan Selangor, 2021)
Coronary artery bypass graft (CABG) is one of the most common surgical procedure to be performed in patients with coronary artery blockages in the world. It was initially performed while the heart was still beating, which is recognized as the off-pump technique (OPCAB). However, after the invention of the cardiopulmonary bypass (CPB) machine, CABG surgery began to be performed while the heart is arrested. The CPB machine, temporarily acting as a heart pump, allowed the establishment of an extracorporeal circulation. This, subsequently, became known as the on- pump technique. It has now become the gold standard of CABG surgery; with significant improvement in overall patient outcome.